The effect of sulfur content in diesel fuel on the reliability of fuel equipment of an automobile engine during the warranty period of operation - M. F. Teterin; R. F. Kalimullin; A. T. Kulakov (Интеллект. Инновации. Инвестиции)
The article is devoted to solving an urgent scientific and practical problem of quantifying the actual state of diesel fuel quality in the Russian Federation and its impact on the operational reliability of automotive equipment.